The Role of Institutional Image in Mediating the Relationship Between Digital Marketing and Perceived Value on the Decision to Private Higher Education - Nana Noviada Kwartawaty (Universitas Negeri Semarang, 2023)
The aim of this research is to analyze the role of institutional image as a mediator in the relationship between digital marketing and perceived value in university selection decisions. This research uses a quantitative approach to investigate causal relationships between different variables and draw general conclusions. In this research, an online survey was used as a data collection method to collect information from students at private universities in Semarang City. A total of 250 questionnaires were distributed to the target group. However, only 200 were properly equipped and met the specified sampling requirements. The data analysis method used in this research is structural equation modeling (SEM). The research results show that digital marketing has a significant influence on college choice decisions in the city of Semarang. Apart from digital marketing, the institutional image variable also has a significant influence on college choice decisions. Meanwhile, the perceived value variable has an insignificant influence on college choice decisions. Hypothesis test results show that institutional image is significantly able to mediate the relationship between digital marketing and choice decisions. Meanwhile, the role of institutional image in mediating the relationship between perceived value and choice decisions has no significant effect